2018
DOI: 10.1108/mi.2018.7913
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, work motivation, burn-out and stress perceptions benefits of a stress management program by autogenic training for emergency room staff: A pilot study

Abstract: Emergency room have particularly stressful work situations. Emergency room personnel cope with stressors on a daily basis. These stressors can be risks factor for burn out and for reduced quality of life and work motivation. Emergency room staff of one of ASP 3 CT urban hospital in Acireale, Italy participated to stress management program by autogenic training twice a month for 16 weeks. This program were prepared based on existing research and studies, and were conducted by clinical psychologists. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…More specifically, the results suggest that the burnout dimensions of exhaustion and cognitive impairment are key in understanding the reduction of these mental health symptoms. In addition, our results show that WRQoL is a significant negative predictor of burnout, which corroborates previous research findings [ 21 , 41 , 42 ]. Moreover, the fact that burnout is a significant positive predictor of mental health symptoms contributes to a growing body of evidence that connects burnout to mental health outcomes such as increased anxiety and depression [ 37 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, the results suggest that the burnout dimensions of exhaustion and cognitive impairment are key in understanding the reduction of these mental health symptoms. In addition, our results show that WRQoL is a significant negative predictor of burnout, which corroborates previous research findings [ 21 , 41 , 42 ]. Moreover, the fact that burnout is a significant positive predictor of mental health symptoms contributes to a growing body of evidence that connects burnout to mental health outcomes such as increased anxiety and depression [ 37 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, our results also emphasize that anxiety could negatively affect the components of social bold and open to change. Healthcare professionals and nurses, in particular, in high anxiety situations tend to not be bold people and may even become a withdrawn person [48,49]. So this anxiety would induce changes in nurses that are derived from physical and psychological exhaustion [50,51]; nurses tend to be less adaptable to changes in their work environment and even less susceptible to patient needs.…”
Section: Discussionmentioning
confidence: 99%
“…All articles in this review were published between 2015 and 2022 with most studies (n=22) based in the USA 1 4 7 17 26 37–53. Two studies were based in Australia,54 55 two in the Netherlands56 57 and one each from Ireland,58 Italy,59 Portugal,60 Brazil,61 Hong Kong,12 Japan62 and Iran 63. Twenty-seven1 4 7 12 26 37–52 54 58–61 63 studies had participants that were predominantly female, two56 57 reported more male than female participants and four17 46 53 55 did not specify gender.…”
Section: Resultsmentioning
confidence: 99%